2023
DOI: 10.1158/1538-7445.sabcs22-gs3-03
|View full text |Cite
|
Sign up to set email alerts
|

Abstract GS3-03: GS3-03 ARV-471, a PROTAC® estrogen receptor (ER) degrader in advanced ER-positive/human epidermal growth factor receptor 2 (HER2)-negative breast cancer: phase 2 expansion (VERITAC) of a phase 1/2 study

Abstract: Background: ARV-471 is a selective, orally administered PROteolysis TArgeting Chimera (PROTAC®) protein degrader that targets wild-type and mutant ER. ARV-471 is being evaluated in patients with ER+/HER2- locally advanced or metastatic breast cancer in a first-in-human phase 1/2 study (NCT04072952). In the phase 1 dose escalation, ARV-471 monotherapy (dose range: 30–700 mg total daily dose) showed a manageable safety profile in patients who had previously received endocrine therapy and a cyclin-dependent kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…The CBR for patients administered 200 mg daily was 37.1%, and for those receiving 500 mg daily, it was 38.9%. Significantly, patients harboring mutant ESR1 exhibited higher CBRs when treated with ARV-471, underscoring its enhanced efficacy in this subgroup (Schott et al, 2023).…”
Section: Tumor Microenvironment-activated Nano-protacsmentioning
confidence: 92%
“…The CBR for patients administered 200 mg daily was 37.1%, and for those receiving 500 mg daily, it was 38.9%. Significantly, patients harboring mutant ESR1 exhibited higher CBRs when treated with ARV-471, underscoring its enhanced efficacy in this subgroup (Schott et al, 2023).…”
Section: Tumor Microenvironment-activated Nano-protacsmentioning
confidence: 92%
“…To date, the limited emerging clinical data from those agents progressing beyond Phase I remains relatively modest in terms of response rates. In the case of ARV-471, Phase II data suggested an overall survival benefit of approximately 3-4 months, and median protein degradation of approximately 70% [175]. In the AR setting, in Phase I studies, ARV-110 showed >50% decrease in Prostate-Specific Antigen (PSA) levels in approximately 16% of the patient population and 2/7 partial responses in the evaluable patient cohort [176].…”
Section: Heterobifunctional Degraders In Oncologymentioning
confidence: 99%
“…Initial efficacy data on a small cohort have already been presented in the past 22 . Further data on a larger cohort in the form of a phase II study have now been presented 23 . The VERITAC study included 71 patients with severely pretreated, advanced HRpos/HER2neg breast carcinoma.…”
Section: Patients With Advanced Hrpos/her2neg Diseasementioning
confidence: 99%
“…Erste Daten zur Wirksamkeit sind an einer kleinen Kohorte bereits in der Vergangenheit vorgestellt worden 22 . Nun wurden weitere Daten an einer größeren Kohorte im Sinne einer Phase-II-Studie vorgestellt 23 . In der VERITAC-Studie wurden 71 Patientinnen mit stark vorbehandeltem, fortgeschrittenen HRpos/HER2neg Mammakarzinom eingeschlossen.…”
Section: Protac Serds Mit Ersten Effektivitätsdaten Aus Einer Phase-i...unclassified